2006
DOI: 10.1007/bf02702044
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of a Himalayan cloudburst event

Abstract: Intense rainfall often leads to floods and landslides in the Himalayan region even with rainfall amounts that are considered comparatively moderate over the plains; for example, 'cloudbursts', which are devastating convective phenomena producing sudden high-intensity rainfall (∼ 10 cm per hour) over a small area. Early prediction and warning of such severe local weather systems is crucial to mitigate societal impact arising from the accompanying flash floods. We examine a cloudburst event in the Himalayan regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(46 citation statements)
references
References 19 publications
0
46
0
Order By: Relevance
“…Deep and severe convective events occurring in the vicinity of mountainous regions leading to anomalous rainfall and subsequent flooding, have been the focus of research for a long time due to their often disastrous outcome for human settlements and ecosystems (Maddox et al, 1978;Caracena et al, 1979;Nair et al, 1997;Das et al, 2003Das et al, , 2006Houze et al, 2011;Webster et al, 2011;Rasmussen and Houze, 2012;Rasmussen et al, 2014). Houze et al (2011) identified the occurrence of a synoptic-scale channel of anomalously moist flow towards the mountain barrier in Pakistan (JulyÁ August 2010) to be responsible for the development of very wide precipitating mesoscale convective systems (MCS) producing huge runoff and flooding.…”
Section: Introductionmentioning
confidence: 99%
“…Deep and severe convective events occurring in the vicinity of mountainous regions leading to anomalous rainfall and subsequent flooding, have been the focus of research for a long time due to their often disastrous outcome for human settlements and ecosystems (Maddox et al, 1978;Caracena et al, 1979;Nair et al, 1997;Das et al, 2003Das et al, , 2006Houze et al, 2011;Webster et al, 2011;Rasmussen and Houze, 2012;Rasmussen et al, 2014). Houze et al (2011) identified the occurrence of a synoptic-scale channel of anomalously moist flow towards the mountain barrier in Pakistan (JulyÁ August 2010) to be responsible for the development of very wide precipitating mesoscale convective systems (MCS) producing huge runoff and flooding.…”
Section: Introductionmentioning
confidence: 99%
“…Thus a large amount of waterflux occurred within a short period of time. As India Meteorological Department (IMD) considers rainfall intensities over 100 mm h -1 as 'cloudburst', this event could also be classified as one 40,41 . Cloudburst takes place when moist and thermodynamically unstable atmosphere rapidly uplifts along a steep topography (e.g.…”
Section: Seasonal Trends In Run-off and Rainfallmentioning
confidence: 99%
“…Das et al (2006) simulated the 6 July 2003 cloudburst that hit Shillagarh in Himachal Pradesh. Their study showed the capability of high-resolution numerical models (nested MM5 with highest resolution of 3 km in the innermost domain) in simulating cloudburst-like systems.…”
Section: Chaudhuri Et Al: Analysis-based Dynamics Of the Uttarkasmentioning
confidence: 99%
“…Even a moderate amount of rain may cause severe events in hills, e.g., flash floods and landslides (Borga et al, 2014). A cloudburst, also known as rain gush or rain gust, is an extreme form of precipitation in which a high intensity of rain falls over a localized area (Das et al, 2006). The India Meteorological Department (IMD) defines cloudburst as a rainfall event with intensity of the order of 100 mm h −1 , accompanied by strong winds and lightning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation